2019
DOI: 10.1002/2211-5463.12719
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes and signaling pathways in chronic obstructive pulmonary disease via bioinformatic analysis

Abstract: Chronic obstructive pulmonary disease (COPD) is a multifactorial and heterogeneous disease that creates public health challenges worldwide. The underlying molecular mechanisms of COPD are not entirely clear. In this study, we aimed to identify the critical genes and potential molecular mechanisms of COPD by bioinformatic analysis. The gene expression profiles of lung tissues of COPD cases and healthy control subjects were obtained from the Gene Expression Omnibus. Differentially expressed genes were analyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 71 publications
(81 reference statements)
1
21
0
Order By: Relevance
“…Ischemia hypoxia induces cardiomyocyte (CM) apoptosis in the process of AMI [31]. It has been reported that cytokine-cytokine receptor interaction was a signi cant pathway in COPD and AMI [24,32]. Compared with healthy controls, TNF-α level was increased in COPD patients and higher TNF-α levels were induced by illness progression [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ischemia hypoxia induces cardiomyocyte (CM) apoptosis in the process of AMI [31]. It has been reported that cytokine-cytokine receptor interaction was a signi cant pathway in COPD and AMI [24,32]. Compared with healthy controls, TNF-α level was increased in COPD patients and higher TNF-α levels were induced by illness progression [33].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of S100A12 by monocytes/macrophages and neutrophils induces proin ammatory responses via ligation with the receptor for advanced glycation end-products (RAGE) and subsequent activation of intracellular signal transduction pathways [63]. S100A12 was identi ed to regulate injury and in ammation of the lung, and play key roles in the pathogenesis of COPD [24]. S100A12 activated airway epithelial cells to produce MUC5AC, which was known to contribute to severe muco-obstructive lung diseases worsening COPD pathogenesis [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the module structure preservation was identified by module preservation R function. Finally, the gene expression profiles of each module were summarized by the module eigengene, and each module eigengene was regressed on COPD trait using the linear model in the limma R package 20 …”
Section: Methodsmentioning
confidence: 99%
“…Finally, the gene expression profiles of each module were summarized by the module eigengene, and each module eigengene was regressed on COPD trait using the linear model in the limma R package. 20 Finally, key COPD genes were acquired by taking the intersection of the overlapped DEGs and hub COPD genes.…”
Section: Identification Of Co-expression Modules and Key Copd Genesmentioning
confidence: 99%